PENGEMBANGAN BAHAN AJAR FISIKA KONTEKSTUAL BERBANTUAN VIRTUAL LAB BERBASIS ANDROID SEBAGAI ALTERNATIF PEMBELAJARAN PADA MASA PANDEMI COVID-19 - Rahmatullah Rahmatullah; Bahtiar Bahtiar; Maimun Maimun (Postgraduate, University of Mataram, 2023)
This study aims to develop effective and efficient contextual physics teaching materials for students and teachers in the Covid-19 pandemic. The teaching materials are based on virtual lab-based Android so that they can be used in any conditions, including when applying physical distancing protocols at school or study from home (SFH). The teaching materials in the form of this application makes it easy for students to access the content on their mobile phones even when they cannot connect to the internet. Also, this application is very easy for teachers to be used. The research method used is based on the 4D model, that is define, design, develop and disseminate. The teaching materials that have been developed passed the first stage test with a Very Good result. The validity test is assessed by expert validators. The subject material used in this study is limited to Reflection and Refraction of Light. The response of students using the teaching materials is Good. According to the students, the teaching materials are easy to use, motivate learning, and deem effective in its implementation